2016
DOI: 10.1097/iae.0000000000001021
|View full text |Cite
|
Sign up to set email alerts
|

Optical Coherence Tomography Angiography of the Macula After Plaque Radiotherapy of Choroidal Melanoma

Abstract: Optical coherence tomography angiography demonstrated significant enlargement of the foveal avascular zone and decreased parafoveal capillary density of both superficial and deep capillary plexuses in eyes after plaque radiotherapy of choroidal melanoma, even in eyes with no clinical evidence of radiation maculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
60
0
19

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 31 publications
5
60
0
19
Order By: Relevance
“…Noticeably, an observer-dependent grading of capillary network integrity was correlated to these morphologic parameters, illustrating the relevance of a clinical grading system based on OCTA in radiation maculopathy, as previously proposed. 15 Although no study has yet compared vascular changes on OCTA following brachytherapy and proton-beam irradiation, a qualitative comparison of our findings with the detailed characteristics reported by Shields et al 14 shows a comparable FAZ enlargement (1.12 vs. 1.25 mm 2 ), after similar mean duration since irradiation (45.1 vs. 46 months). Authors have also reported vascular densities based on a custom method before it became standardized in OCTA devices, which prevents reliable comparison.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Noticeably, an observer-dependent grading of capillary network integrity was correlated to these morphologic parameters, illustrating the relevance of a clinical grading system based on OCTA in radiation maculopathy, as previously proposed. 15 Although no study has yet compared vascular changes on OCTA following brachytherapy and proton-beam irradiation, a qualitative comparison of our findings with the detailed characteristics reported by Shields et al 14 shows a comparable FAZ enlargement (1.12 vs. 1.25 mm 2 ), after similar mean duration since irradiation (45.1 vs. 46 months). Authors have also reported vascular densities based on a custom method before it became standardized in OCTA devices, which prevents reliable comparison.…”
Section: Discussionsupporting
confidence: 66%
“…After plaque brachytherapy, Veverka et al 15 describe gradual alterations of the macular microvasculature on OCTA. Shields et al 14 have reported a decreased capillary density in both plexuses, as well as FAZ enlargement. Finally, Say et al 25 have reported decreased capillary density in irradiated eyes without clinically patent maculopathy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Currently, OCT-A is the most sensitive method with which to detect radiation maculopathy [3,13]. In fact, in a recent study of 65 patients, Shields et al [14] identified parafoveal changes on OCT-A. Here, we report the extent of changes in the superficial capillary plexus, which included the reduction in CVD in all ETDRS sectors.…”
Section: Discussionmentioning
confidence: 82%
“…The OCT probe insertion-induced edema should be much lower or absent in humans due to availability of dedicated esophageal OCT catheters that can be inserted in a deflated state 32 and because of the larger size of the organ. Previous studies investigated the use of OCT in esophageal and radiation-induced damages, 20,[33][34][35][36][37][38][39][40][41][42][43][44][45][46] the visibility of esophageal layers in OCT images, and the differentiation between healthy and cancerous esophagus. [39][40][41] Esophageal OCT has been used to detect Barrett's esophagus in various studies.…”
Section: Discussionmentioning
confidence: 99%